Intended and unintended impacts of the comprehensive reform of urban public hospitals: A mixed-method study in Hangzhou, China - Zhang, Tao; Liu, Jing; Lu, Beiyin; Yan, Zhongheng; Huang, Xiaojun; Lu, Wei (Frontiers in Public Health, 2022)
Objectives: Public hospital reform is key area in the Chinese healthcare system reform with aim of controlling unreasonable growth of medical expenditures. This study aims to evaluate impacts of two rounds of urban public hospital reforms respectively starting in 2018 and 2019. Method: A mixed-method method was conducted in Hangzhou, China. In quantitative phase, monthly data covering 7 provincial, 12 municipal and 35 district hospitals from March 2017 to June 2020 was analyzed using a panel-interrupted time-series. Thematic content analysis was conducted using qualitative data from 32 in-depth interviews. Results: Quantitative data showed a large reduction in the proportion of drug revenue (provincial hospitals: -4.937%; municipal hospitals: -2.765%; district hospitals: -2.189%) and increase in the proportion of consumable (provincial hospitals: β2=2.025; municipal hospitals: β3=0.206) and examinations (provincial hospitals: β2=1.354, β3=0.159; municipal hospitals: β2=1.179) revenue after the first reform. In post-reform 2, The respective instant decrease and increase in the proportion of consumable (provincial hospitals: -2.395%; municipal hospitals: -0.898%) and medical services (provincial hospitals: 2.115%; municipal hospitals: -2.604%) revenue were observed. Additionally, quantitative and qualitative data indicated inpatient expenditures dropped considerably after reform. However, insufficient compensation for medical services and increased financial pressure on hospitals were repeatedly mentioned as unintended consequences in qualitative interviews. Conclusions: Overall, the urban public hospital reforms in China created positive effects in adjusting hospital revenue structure and constraining soaring medial expenditures. Unintended consequences remind policymakers of establishing rational and dynamic compensation mechanism for public hospitals.